2013
DOI: 10.4103/1658-354x.115334
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient endoscopic retrograde cholangiopancreatography: Safety and efficacy of anesthetic management with a natural airway in 653 consecutive procedures

Abstract: Background:Endoscopic retrograde cholangiopancreatography (ERCP) is a unique diagnostic and therapeutic procedure performed in high risk patients in prone/semi-prone position. Propofol based deep sedation has emerged as the method of choice however, the ability to predict possible complications is yet un-explored.Aims:The present study aimed to evaluate known high risk-factors for general anesthesia (American Society of Anesthesiologists (ASA) status, body mass index (BMI), and Mallampati class) for their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Airway complications like obstruction and apnea under deep sedation are known to be primarily dependent upon the depth of anesthesia rather than patient physical status alone. [18,19] As all our patients were in lateral position, the chances of upper airway obstruction due to tongue fall were less; in case of transient desaturation, most patients responded to increased oxygen supplementation in addition to dose readjustments, with saturations returning to baseline. In patients with LVAD, if oxygen saturation does not respond to the above measures, a possibility of right ventricular dysfunction must be considered.…”
Section: Discussionmentioning
confidence: 95%
“…Airway complications like obstruction and apnea under deep sedation are known to be primarily dependent upon the depth of anesthesia rather than patient physical status alone. [18,19] As all our patients were in lateral position, the chances of upper airway obstruction due to tongue fall were less; in case of transient desaturation, most patients responded to increased oxygen supplementation in addition to dose readjustments, with saturations returning to baseline. In patients with LVAD, if oxygen saturation does not respond to the above measures, a possibility of right ventricular dysfunction must be considered.…”
Section: Discussionmentioning
confidence: 95%
“…This sentiment was examined by Coté et al demonstrating significant risk for ASA scoring ≥3 predicting the need for airway maneuvers during advanced endoscopic procedures [33]. Other retrospective analyses have evaluated ASA scoring as a risk for serious AE in the setting of therapeutic endoscopy [34, 35]. As a result, most prior studies evaluating ASC therapeutic endoscopy either included a minimal number of individuals with ASA classes ≥III or excluded them entirely [318].…”
Section: Discussionmentioning
confidence: 99%
“…Age, male sex, comorbidities, fentanyl use, ASA classification, and BMI were previously reported as independent risk factors for respiratory events during UGI endoscopy [1, 2, 16, 17]. In contrast, Goudra et al [18] found no increased risk for hypoxaemia in patients with a higher ASA classification or BMI when patients were pre-oxygenated with 100 % oxygen prior to drug administration and received an airway device to maintain a patent airway. Our study shows that a hypoxaemic episode was preceded by apnoea in only in 34 % of the cases, with a delay of about 40 s between apnoea and the development of hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%